1992
DOI: 10.1055/s-0038-1648520
|View full text |Cite
|
Sign up to set email alerts
|

A Soluble Recombinant Factor VIII Fragment Containing the A2 Domain Binds to Some Human Anti-Factor VIII Antibodies that Are not Detected by Immunoblotting

Abstract: SummaryHuman factor VIII (f VIII) inhibitors are pathologic antibodies that inactivate fVIII. A cDNA clone was modified to encode f VIII amino acid residues 373-740 for expression in a baculovirus vector in insect cells. The encoded protein fragment H2 was produced as a soluble, secreted protein, and it was used to test inhibitor plasmas for the presence of antibodies that were not detected by immunoblotting. Seven of 13 inhibitors that bound, only to the fVIII light chain by immunoblotting also bound to fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 14 publications
2
50
0
Order By: Relevance
“…Its activity was determined in the one-stage clotting assay (33) to be 3300 units/mg, which is similar to a previously reported value (31). The recombinant C2 domain was produced as a soluble, secreted protein in Spodoptera frugiperda Sf9 insect cells (34), and it was purified by gel filtration and ion-exchange chromatography (21). vWf was purified from cryoprecipitate (Cutter Biological) (21).…”
Section: Methodssupporting
confidence: 72%
“…Its activity was determined in the one-stage clotting assay (33) to be 3300 units/mg, which is similar to a previously reported value (31). The recombinant C2 domain was produced as a soluble, secreted protein in Spodoptera frugiperda Sf9 insect cells (34), and it was purified by gel filtration and ion-exchange chromatography (21). vWf was purified from cryoprecipitate (Cutter Biological) (21).…”
Section: Methodssupporting
confidence: 72%
“…Recombinant A2 domain polypeptides 336-606 (20) and 373-740 (10) were able to neutralize the FVIII inhibitory activity of a number of anti-A2 antibodies. Competition immunoradiometric assays in which several inhibitor IgG preparations were evaluated for inhibition ofbinding ofa radiolabeled inhibitor IgG to recombinant A2 have indicated that, despite the large region that currently defines the A2 epitope, anti-A2 inhibitors appear to bind to the same or to closely spaced epitopes (7). The above results suggest that a common inhibitor epitope is located within residues 373-606 of the A2 domain.…”
mentioning
confidence: 95%
“…Inhibitor IgG was prepared as described previously. 14 The inhibitors in HR, LK, AA, and RvR antibodies were specific for the C2 domain on antibody neutralization assays. 2 AJ was identified as C2 specific by using a panel of recombinant hybrid human/porcine fVIII molecules.…”
Section: Introductionmentioning
confidence: 99%